Syndromic cardiac disorder is associated with a non-coding deletion that induces a 3D chromatin remodeling and PITX2 expression dysregulation. (3rd October 2022) - Baudic, M; Murata, H; Bosada, F M; Souto Melo, U; Aizawa, T; Guedon, A; Lindenbaum, P; Gourraud, J B; Makita, N; Mundlos, S; Christoffels, V M; Makiyama, T; et al.
Abstract:  : In a first family (family#1), we identified 53 members of whom 17 present a syndromic cardiac disorder characterized by electrical disorders (sinus node dysfunction, atrial fibrillation...) and developmental defects (atrial septal defect, valvopathy, left ventricle non-compaction...) following an autosomal dominant model. Among the affected family members, 6 are implanted with a pacemaker and one experienced a sudden death at 43yo. Despite a strong linkage pointing to the 4q25 region, exome sequencing failed to identify causal variant. Interestingly, 6 additional non-related families presenting the same phenotype have been also identified. Our aims are to identity the causal mutation and the molecular mechanism underlying this complex cardiac syndrome. Genetic study has been performed using whole genome sequencing (WGS). Based on transgenic mouse strains, we assessed the impact of Family#1 mutation on the phenotype and on gene expression. Then, we generated human cardiomyocytes derived iPS cells (CM-iPS) isogenic models to evaluate the epigenome (CUT&RUN and ATAC-seq), transcriptome (RNA-seq) and topological associated domain (TAD) remodelling (Hi-C). By WGS we uncovered a deletion of 15kb in a gene desert area on 4q25, segregating in all affected relatives of Family#1. The 6 other families present overlapping deletions. Mouse model recapitulates the cardiac phenotype and exhibit a dysregulation of Pitx2 expression in cardiac specific compartments. Based on human CM-iPS models, epigenetic data highlight among the 15kb deletion a unique open region containing a CTCF binding site, crucial for delimiting TAD boundaries. Hi-C assay reveals the fusion of 2 TADs and highlights new interactions between PITX2 and atrial specific regulatory elements. We identified a deletion located within a gene desert area associated with a complex cardiac disorder. The CTCF binding site contained in the deletion seems key in the TAD border. The TAD remodelling leads to new (regulatory) interactions and expression dysregulation of PITX2. We describe a new molecular mechanism implying a yet unidentified non-coding regulatory element of PITX2 and responsible for a complex electrical and developmental cardiac syndrome. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Nantes UniversitéFrench national reserch agency (ANR)